2016
DOI: 10.1111/jfq.12187
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mulberry Leaf Extracts on Color, Lipid Oxidation, Antioxidant Enzyme Activities and Oxidative Breakdown Products of Raw Ground Beef During Refrigerated Storage

Abstract: The study investigated the effects of mulberry leaf extracts (MLE) on the color, lipid oxidation, antioxidant enzyme activities and oxidative breakdown products of raw ground beef during refrigerated storage. The five treatments were: MLE at 0, 100, 500 and 1,000 lg/g muscle (C, low concentration mulberry leaves extracts (LM), medium concentration mulberry leaves extracts (MM) and high concentration mulberry leaves extracts (HM)) and positive control with 20 lg Vitamin E/g muscle (VE). MLE maintained color, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 43 publications
(61 reference statements)
0
34
0
1
Order By: Relevance
“…Similar result was reported by Zhang et al . (), who found that the higher activities of total SOD and GSH‐px were detected in raw beef treated with mulberry leaf extract compared to that of control during refrigerated storage. The different protective effect on antioxidant enzyme activities was observed in treatments of Ch + clo, Ch + cin and Ch + lem, which might considerably depend on the components of essential oils.…”
Section: Resultsmentioning
confidence: 97%
“…Similar result was reported by Zhang et al . (), who found that the higher activities of total SOD and GSH‐px were detected in raw beef treated with mulberry leaf extract compared to that of control during refrigerated storage. The different protective effect on antioxidant enzyme activities was observed in treatments of Ch + clo, Ch + cin and Ch + lem, which might considerably depend on the components of essential oils.…”
Section: Resultsmentioning
confidence: 97%
“…The color of meat products and meat is influenced by metmyoglobin percentage in muscle. Initially, the myoglobin was changed into oxymyoglobin (light pink color), which could result in brighter red meat, and then oxymyoglobin was oxidized into metmyoglobin during storage [7].…”
Section: Color Stabilitymentioning
confidence: 99%
“…1,1,3,3-tetraethoxypropane was used to develop the standard curve for TBARS assay. TBARS values were reported as mg of malonaldehyde per kg of beef burger [7].…”
Section: Determination Of Lipidmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthetic antioxidants such as BHT, TBHQ, and BHA have demonstrated various adverse effects on the human health including allergy, headache, asthma, and dermatitis. Recent studies on the utilization of natural antioxidants (e.g., herbal essential oils and extracts) indicate their capacity and safety [3,4]. Also, the antimicrobial properties of natural substances such as plant essential oils and extracts have been extensively studied with promising results [5].…”
mentioning
confidence: 99%